English pronunciation in use : Intermediate (Self-study and classroom use) - Hancock, Mark (Cambridge Cambridge University Press, 2003)
Self-diagnostic tests at Intermediate and Advanced levels help learners identify and focus on their own pronunciation problems. Additional reference section includes a learner-friendly answer key, fun exercises to practise phonemic symbols, a guide for speakers of specific languages, exercises on minimal pairs and a glossary of specialised terms.
Keywords: Ngôn ngữ Anh